Spatial functionality in the architectural design of single-family homes: Case Urbanización Lotes del Valle - Requelme Parrales, Genesis Elizabeth (2025)
This study evaluates spatial functionality in two-story single-family homes located in the Lotes del Valle residential development in Portoviejo, Ecuador, with the aim of analyzing the adequacy of architectural design in relation to users’ actual needs. Using a mixed-methods approach and an exploratory-descriptive design, quantitative techniques (Likert-scale surveys) and qualitative methods (semi-structured interviews and direct observation) were combined to obtain a comprehensive understanding of the residential experience. The sample consisted of ten homes, whose spatial characteristics were compared against the standards established by the NEC-HS-AU regulation on Universal Accessibility. The results reveal moderate to low levels of satisfaction, particularly in bathrooms and bedrooms, where the lack of storage and the inadequate relationship between furniture and space dimensions negatively affect users’ comfort. In contrast, kitchens and social areas received higher evaluations. A clear mismatch was identified between users’ expectations and the solutions offered by conventional housing models, which are often characterized by limited flexibility and customization. The study concludes that functionality, together with adaptability and user participation, are key factors in enhancing habitability. It is recommended that future residential designs integrate participatory processes from early planning stages and explore the use of emerging technologies such as parametric design and augmented reality to expand customization options in social housing projects.